A synthetic approach to the classification of music. Review article - Szostak, Rick (El profesional de la informacion, 2020)
This paper first reviews the advantages and disadvantages associated with both pre-coordination and post-coordination in classification. It then argues that we can have the advantages of both if we couple a post-coordinated (synthetic) approach to classification with a user interface that privileges the word order in search queries. Several other advantages of such an approach to classification and search are reviewed. It better captures the nature of a work (or object), addresses important issues with respect to social diversity, and facilitates user queries. It produces subject strings that resemble sentence fragments; this serves to clarify the meaning of terms within the subject string, and makes subject strings more comprehensible since humans typically think in sentences. These various benefits are then illustrated in the classification of works of music. It is shown that many important characteristics of works of music are best handled by such a system. These are generally poorly addressed, or not addressed at all, by existing approaches to the classification of music.